2015
DOI: 10.1177/1049732315575708
|View full text |Cite
|
Sign up to set email alerts
|

The Symbolic Value and Limitations of Racial Concordance in Minority Research Engagement

Abstract: The well-documented underrepresentation of racial and ethnic minorities in research demands action. The field of health disparities research, however, lacks scientific consensus about how best to respectfully recruit underrepresented minority populations in research. We explore the investigators’ perspective regarding how their own racial and ethnic background influenced their ability to recruit minorities, including 1) the influence of racial concordance (“race-matching”) in research recruitment, 2) attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 36 publications
1
91
0
Order By: Relevance
“…In RECRUIT, sixty percent of the specialist investigators and 71% of coordinators were non-Hispanic white. Data from the Parkinson’s disease minority recruitment trial 31 and other studies 50 cast some doubt on the need for racial and ethnic concordance between specialist investigators and potential trial participants. In the Parkinson’s disease trial 31 the high minority enrolling specialist investigators and coordinators were predominantly Caucasian non-Hispanic.…”
Section: Resultsmentioning
confidence: 99%
“…In RECRUIT, sixty percent of the specialist investigators and 71% of coordinators were non-Hispanic white. Data from the Parkinson’s disease minority recruitment trial 31 and other studies 50 cast some doubt on the need for racial and ethnic concordance between specialist investigators and potential trial participants. In the Parkinson’s disease trial 31 the high minority enrolling specialist investigators and coordinators were predominantly Caucasian non-Hispanic.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research suggests that engaging key opinion leaders, community stakeholders, and/or community coalitions in recruitment and delivery of an intervention are advantageous strategies to enhance participant recruitment and engagement [63, 70]. Matching study staff to the demographic characteristics of a target population can also be enhance participant engagement [71, 72], as AA women enjoy to socialize and receive health information from women they perceive as similar or “like” themselves [13, 73, 74]. For example, if the goal a program is to promote PA among older low-income AA women, hiring older low-income women AA women to recruit and deliver the PA program is advised.…”
Section: Resultsmentioning
confidence: 99%
“…This writer, a Black middle-class man (lead author of this paper) and a Black middle-class woman (second author) facilitated the focus groups with the support of graduate research assistants who took detailed notes. Race and gender matching focus group facilitators has been documented as a best practice in qualitative research as matching has been shown to improve rapport and promote more authentic responses [66]. Focus group questions included but were not limited to the following: "Describe some of the stressors that you experience?…”
Section: Data Collection and Recruitmentmentioning
confidence: 99%